1995
DOI: 10.1681/asn.v5111940
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization among United States dialysis patients

Abstract: Measurements of hospitalization in the dialysis population are important because they provide insight into the morbidity and the cost of treatment among dialysis patients. Prior comparisons of hospitalization for different dialysis modalities have had conflicting results. This study was designed to compare hospitalization for patients treated with peritoneal dialysis (PD) versus hemodialysis (HD) using the data from the U.S. Renal Data System 1993 Annual Data Report. The study population included all Medicare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Hospitalization has economic implications as well as association with negative effects on QoL 73 . As with most comparisons between HD and PD, some studies have shown comparable hospitalization rates, 74 some have reported higher hospitalization rates in PD, 73,75 while others have found hospitalization rates to be lower in PD 76,77 . A Canadian study of 822 consecutive dialysis patients found that comparative hospitalization rates are heavily dependent on the analytic starting point and on whether intention‐to‐treat (ITT) or treatment‐received analyses are used 78 .…”
Section: Pd Outcomesmentioning
confidence: 99%
“…Hospitalization has economic implications as well as association with negative effects on QoL 73 . As with most comparisons between HD and PD, some studies have shown comparable hospitalization rates, 74 some have reported higher hospitalization rates in PD, 73,75 while others have found hospitalization rates to be lower in PD 76,77 . A Canadian study of 822 consecutive dialysis patients found that comparative hospitalization rates are heavily dependent on the analytic starting point and on whether intention‐to‐treat (ITT) or treatment‐received analyses are used 78 .…”
Section: Pd Outcomesmentioning
confidence: 99%
“…Studies have suggested a relationship between the frequency and cost of hospitalisations and specific treatment modalities [ 13 16 ]. A few cost studies have also compared the delivery of dialysis treatments across different locations, noting the increased infrastructure and recurrent costs per patient per year associated with remote based services [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hospitalization rate was calculated as the annual number of residents in a defined area hospitalized with a positive SARS-CoV-2 laboratory test divided by the number of patients classified as critical within that defined area [ 8 ], expressed as n (%) hospitalizations per 100 patient-years [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…e hospitalization rate was calculated as the annual number of residents in a defined area hospitalized with a positive SARS-CoV-2 laboratory test divided by the number of patients classified as critical within that defined area [8], expressed as n (%) hospitalizations per 100 patient-years [9]. e drop-out rate was calculated as the annual number of people who discontinued peritoneal dialysis divided by the total number of peritoneal dialysis patients for the same year and is expressed as n (%), representing the number of drop-outs per 100 patient-years.…”
Section: Definition and Calculation Of Indicatorsmentioning
confidence: 99%